Profile of Problem-Solving Skills Question Story based on the Polya Model at Kampus Mengajar Partner Schools - Mufadillah, Mufadillah; Trimurtini, Trimurtini; Supriyanto, Teguh (Numerical (Online), 2024)
The Kampus Mengajar Program is a government policy aimed at students to provide innovations to problems in partner schools in the teaching and learning process. The problem is that in learning, no attention is paid to students' problem-solving skills when working on story problems. This study aims to describe and analyze the problem-solving skills of story problems on beam volume material for grade IV students in one of the Kampus Mengajar partner schools in Pemalang Regency, SD N 3 Kedungbanjar. The qualitative approach is descriptive, involving 28 students and focusing on three students representing high, medium, and low abilities. Data collection used tests, documentation, and interviews. The instruments used were two problem-solving test questions, interview guidelines, and a rubric for assessing problem-solving skills based on the stages of the Polya Model (understanding the problem, planning a solution, implementing a solution plan, and checking back). The results showed that students with low average test scores still had difficulties in the stages of Polya's Model. Many students did not use all four stages of problem-solving entirely and correctly. Students had difficulty at the recheck stage, with the percentage of students who went through the stage only amounting to 18.75%. Based on the high, medium, and low category subjects, it shows that (1) High-skills subjects can complete all stages of Polya Model problem-solving. (2) Moderate skills subjects have not been able to complete all stages of Polya Model problem-solving by skipping the checking backstage. (3) Low-skills subjects were only able to go through the stages of making and implementing a solution plan by skipping the stages of understanding the problem and checking back. Development recommendations are expected to be needed to improve the results and process of problem-solving skills.